The Effect Of Nutrition Education On Adolescent Knowledge About The Importance Of Breakfast - Tri Marta Fadhilah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Breakfast is an eating activity that is carried out from waking up to 9 in the morning to meet some of the daily nutritional needs. Breakfast is one of the factors that affect the concentration of learning. the research objective was to determine the effect of nutrition education on adolescent knowledge regarding the importance of breakfast. The method used is nutrition counseling using questionnaires, PowerPoint, Food Models, Standing Banners, and e-Books. The results of the pre-test and post-test analysis show that there is a significant difference between the level of knowledge of adolescents before and after education. The results showed that the average pre-test score was 76.04 and the post-test average score was 81.676. The percentage increase in pre-test and post-test scores is 7.4%. After the Wilcoxon test was carried out, a p-value of 0.0001 (α; 0.05) was obtained. Based on the results of the analysis, it shows that there is a significant difference, which means that there is an increase in adolescent knowledge regarding the importance of breakfast and its relation to academic achievement.